A hydrolytically stable cage-based metal–organic framework containing two types of building blocks for the adsorption of iodine and dyes. Issue 4 (22nd December 2020) - Wang, Guang-Qing; Huang, Jie-Fen; Huang, Xiao-Feng; Deng, Shu-Qi; Zheng, Sheng-Run; Cai, Song-Liang; Fan, Jun; Zhang, Wei-Guang
Abstract : A metal–organic framework (SCNU-Z4) with high chemical stability in water and common organic solvents showed ability for iodine and dye adsorption. Abstract : Metal–organic frameworks (MOFs) with high chemical stability in solution are of great interest and have potential for the removal of environmental contaminants. Herein, a MOF (SCNU-Z4) possessing a cage cavity and channels based on Cu(ii ) and a bifunctional tripodal nitrogen-donor ligand has been constructed and used to capture I2 molecules and hazardous dyes in solution. The truncated octahedron cage in SCNU-Z4 is similar to that in the well-known M-BTT (H3 BTT = 1, 3, 5-benzenetristetrazolate) MOFs but is composed of both trinuclear and tetranuclear SBUs. The BET test showed that both micropores and mesopores were observed in the crystal sample, and it showed potential ability for CO2 /N2 separation. This MOF shows high stability in aqueous solution with a pH ranging from 3 to 11 and in various organic solvents. Due to the porous framework, uncoordinated N donor and hydrolytic stability, the I2 and aqueous-phase dye adsorption applications of SCNU-Z4 were explored. The results indicate that SCNU-Z4 can capture I2 in both cyclohexane and aqueous solutions, and the absorption capacity is approximately 237 mg g −1 and 332 mg g −1, respectively. Dye adsorption experiments showed that it can absorb both anionic and cationic dyes. The adsorption of a mixed MO & MLB solution showed a synergistic effect. The separation of MLB & RhB and MLB & CR can be achieved by size-dependent and kinetic-dependent modes, respectively. SCNU-Z4 showed the best adsorption towards CR. This MOF exhibits a high adsorption capacity of 1200 mg g −1, which is among the best for MOFs, and the adsorption kinetics are faster than those of other selected dyes. A mechanistic study revealed that the high capacity can be attributed to the hydrogen bonding and π⋯π interactions between the SCNU-Z4 host and CR guest molecules. Unexpectedly, SCNU-Z4 also showed a moderate adsorption capacity for the large AB dye molecule. The adsorption capacity of SCNU-Z4 for AB reached 221 mg g −1, which is far beyond its self-decomposition. The adsorption may be due to the surface adsorption and mesopores that are generated from the defects of SCNU-Z4. The good adsorption performance of SCNU-Z4 is caused by the cage-like framework, diverse pores and interaction sites.